Mapping Students’ Misconceptions in Momentum and Impulse: A Systematic Literature Review of Conceptual Understanding and Instructional Interventions - Dhinar Asri Intantri; Sutopo Sutopo; Nasikhudin Nasikhudin; Sentot Kusairi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to identify and analyze students’ misconceptions regarding momentum and impulse through a Systematic Literature Review (SLR), focusing on patterns of misconceptions, difficulties in conceptual understanding, and effective instructional interventions reported in previous studies. Methodology: This study employed a PRISMA-based Systematic Literature Review design. Articles were collected from Scopus-indexed journals, SINTA-accredited journals, ERIC, Taylor & Francis, ResearchGate, and Google Scholar published between 2018 and 2025. The article selection process used purposive sampling based on predefined inclusion and exclusion criteria. From 1,032 identified articles, 8 eligible studies were selected for analysis. Data were collected through document analysis and analyzed using thematic analysis and narrative synthesis. Main Findings: The findings indicate that students’ conceptual understanding of momentum and impulse remains low, while misconceptions persist in force–time–impulse relationships, graphical interpretation, momentum conservation, and momentum–energy integration. Most misconceptions originate from an incomplete understanding of Newtonian mechanics and fragmented conceptual structures. Several instructional approaches, including multiple representations, knowledge integration, cognitive conflict, conceptual change text, and demonstration-based learning, were found effective in reducing misconceptions and improving conceptual understanding. Novelty/Originality of this study: This study provides a focused synthesis of misconception patterns specifically in momentum and impulse topics and emphasizes the importance of conceptual integration-based instruction in reducing persistent misconceptions in physics learning.